The Impact of Customer Relationship Management on Sustainable Competitive Advantage Mediator Brand Citizenship Behavior: An Analytical Study in a Sample of Iraqi Banks - Sabah alchalabi, Alzahraa; Hammood Chitheer , Saadoon (Journal of Economics and Administrative Sciences, 2024)
The research aims to study the impact of customer relationship management on sustainable competitive advantage through brand Citizenship Behavior in a sample of Iraqi banks. The main problem of the research is summarized in the following questions: "have bank leaderships been able to employ customer relationship management in achieving sustainable competitive advantage? And have they been able to maximize this impact through the mediating role of brand Citizenship Behavior?" The comprehensive survey method was used to collect data, given the importance of the banking sector, both government and private banks in Baghdad were chosen as the focus of this study. Commercial and Islamic banks were considered for examination, and the researcher conducted field visits to six banks, including Rafidain Bank, Trade Bank of Iraq, Alnahrain Islamic Bank, Al Taif Islamic Bank, Iraqi Middle East Investment Bank, National Bank of Iraq. The research sample comprised 212 employees from these banks. Data analysis and hypothesis testing were conducted using appropriate statistical tools with the help of (SPSS and AMOS) software. The results revealed a significant impact of customer relationship management on sustainable competitive advantage through the mediating role of brand Citizenship Behavior.